Aquaporins Are Essential to Maintain Motility and Membrane Lipid Architecture During Mammalian Sperm Capacitation - Delgado-Bermúdez, Ariadna; Recuero, Sandra; Llavanera, Marc; Mateo-Otero, Yentel; Sandu, Andra; Barranco, Isabel; Ribas-Maynou, Jordi; Yeste, Marc (Frontiers in Cell and Developmental Biology, 2021)
Aquaporins are a family of ubiquitous transmembrane proteins that allow the transport of water and small molecules across the cell plasma membrane. The different members of this family present a characteristic distribution across different cell types, which is species-specific. In mammalian sperm, different AQPs, including AQP3, AQP7 and AQP11, have been identified; their main roles are related to osmoadaptation and sperm motility activation after ejaculation. Capacitation, which is a post-ejaculatory process that sperm must undergo to achieve fertilizing ability, is triggered by pH changes and different extracellular ions that are present in the female reproductive tract. Considering the function of AQPs and their influence on pH through the regulation of water flow, this study aimed to elucidate the potential role of different AQPs during in vitro sperm capacitation using three different transition metal compounds as AQP inhibitors. Cooper sulphate, a specific inhibitor of AQP3, caused a drastic increase in peroxide intracellular levels compared to the control. Mercury chloride, an unspecific inhibitor of all AQPs except AQP7 produced an increase in membrane lipid disorder and led to a decrease in sperm motility and kinetics parameters. Finally, the addition of silver sulfadiazine, an unspecific inhibitor of all AQPs, generated the same effects than mercury chloride, decreased the intracellular pH and altered tyrosine phosphorylation levels after the induction of the acrosome reaction. In the light of the aforementioned, a) the permeability of AQP3 to peroxides does not seem to be crucial for sperm capacitation and acrosome reaction; b) AQPs have a key role in preserving sperm motility during that process; and c) AQPs as a whole seem to contribute to the maintenance of lipid membrane architecture during capacitation and may be related to the intracellular signaling pathways involved in the acrosome reaction. Hence, further research aimed to elucidate the mechanisms underlying the involvement of AQPs in mammalian sperm capacitation and acrosome reaction is warranted.